The «Archivo Agrario»: problem and possibility - Adrianzén Ponce, Cayetana (2022)
Archives provide the basis for national historical narratives, a premise for nation-building. However, Peru’s government administration problems extend to national archives: insufficient maintenance resources and inadequate service to the public. This creates a duality (i.e., enormous potential yet bad services), which is especially noticeable in the «Archivo Agrario». Collected in the 1970s by Peruvian researchers, the «Archivo Agrario» is unique in Latin America, given the variety and origin of the documents. In this essay, and using my research as an example, I explore the challenges and, more importantly, the opportunities afforded by this archive —and the urgent need to transform it radically.